Pendampingan Deteksi Dini Tumbuh Kembang Anak pada Guru dan Wali Murid RA Muslimat NU Gembong Pati - Ari Purnomo Endah Aflahani; Indah Sa'adah (JURNAL LENTERA ANAK, 2021)
This community service aims to provide understanding as well as provision for partners, namely the father and mother of teachers and guardians of KB students, Shofa Azzahro and RA Muslimat NU in Gembong District, especially in Gembong Village. The material presented was in the form of mentoring for Early Detection of Child Growth and Development for Teachers and Guardians of RA Muslimat NU Gembong Pati in accordance with the Ministry of Health's SDIDTK (Simulation of Early Detection of Growth and Development) Interventions to improve the understanding of teachers and guardians of students in early detection of growth and development. The implementation method includes socializing the definition, the importance of early detection and assistance in accordance with the SDIDTK book with direct practice. The method of implementing community service that has been carried out consists of three stages. The first stage is the socialization and preparation of Assistance for Early Detection of Child Growth and Development in accordance with SDIDTK. The second stage is the training of Assistance for Early Detection of Child Growth and Development in accordance with the Ministry of Health's SDIDTK. Our hope after the implementation of this service is that there will be an increase in applying Assistance for Early Detection of Growth and Development, so that when there is a delay, developmental deviations are immediately detected. The results of the dedication of teachers and guardians of students are enthusiastic in participating in mentoring and immediately applying them to their respective students.